THE DEVELOPMENT OF PREZI APPLICATION-BASED LEARNING MEDIA ON ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SMP MUHAMMADIYAH 02 MEDAN - Wahiddin Wahiddin; Mesiono Mesiono; Haidir Haidir (Pusat Penerbitan Universitas (P2U) Unisba, 2022)
The objective of this study is to provide realistic, practical, and effective Prezi application-based learning media in PAI subjects in order to improve students' comprehension ability. This is a development study using the ADDIE development model. The research participants were 15 students from VIII-1 and 15 students from VIII-2. The study's findings revealed that the validity of the learning media generated was assessed based on the validity of the learning media by the validators, with a total average value of 3.73 (